A polysulfide radical anions scavenging binder achieves long‐life lithium–sulfur batteries. Issue 3 (22nd June 2022) - Wang, Chengdong; Ma, Yue; Du, Xiaofan; Zhang, Huanrui; Xu, Gaojie; Cui, Guanglei
Abstract: Fast capacity decay caused by the polysulfide shuttle is the primary cause to impede the practical application of lithium–sulfur (Li–S) batteries. The polysulfide shuttle involves the evolution of polysulfide dianions (Li2 S x, x = 3–8) and radical anions (S n – ) during the charge‐discharge process. Despite good efforts have been made to suppress polysulfide shuttle, the electrolyte depletion caused by the attack of polysulfide radical anions, which results in rapid battery aging, has been almost ignored. To address this challenge, based on a two‐prolonged design philosophy, we demonstrate a polylysine‐derived cathode binder with a free radical‐scavenging function, lipoic acid‐grafted ε‐polylysine (EPL‐g‐Lipo), where abundant amide and amine groups in the ε‐polylysine component possess a high polysulfide affinity, while lipoic acid motifs offer an excellent polysulfide radical anions‐scavenging ability. As a result, Li–S batteries with EPL‐g‐Lipo binder display superior cycling stability to poly(vinylpyrrolidone) binder‐based counterparts, mainly ascribed to its powerful shuttle suppression effect and free radicals scavenging ability. This study states the importance of designing multifunctional binders for performance improvements of Li–S batteries. Abstract : The shuttle effect of polysulfide dianions and radical anions (S n – ) generated from the disproportionation of long‐chain polysulfides (Li2 S y, y = 5–8) induces the rapid capacity decay of the Li–S battery. A lipoic acid‐grafted ε‐polylysine (EPL‐g‐Lipo) binder with free radical‐scavenging and polysulfide fixing functions is developed to suppress the shuttle effect. Therefore, superior electrochemical performance is achieved for Li–S battery.